Cost-effectiveness of first-line enfortumab vedotin in addition to pembrolizumab for metastatic urothelial carcinoma in the United States - Li, Andong; Wu, Meiyu; Xie, Ouyang; Xiang, Heng; Meng, Kehui; Tan, Chongqing; Wang, Long; Wan, Xiaomin (Frontiers in Immunology, 2024)
The EV-302 trial found that the combination of enfortumab vedotin (EV) with pembrolizumab significantly improved survival for patients with metastatic urothelial carcinoma (mUC). However, given the high cost of the drugs, there is a need to assess its value by considering both efficacy and cost.This study assessed the cost-effectiveness of EV plus pembrolizumab as a first-line treatment for patients with mUC from the perspective of U.S. payers.Methods: A Markov model was developed to compare the lifetime costs and effectiveness of EV in combination with pembrolizumab with chemotherapy in the treatment of mUC patients from U.S. payer perspective. Life-years (LYs), quality-adjusted LYs (QALYs), and lifetime costs were estimated. One-way, two-way and probabilistic sensitivity analyses were conducted to evaluate model uncertainty.Additionally, subgroup analyses were performed.Results: Compared to chemotherapy, the combination of EV and pembrolizumab provided an additional 2.10 LYs and 1.72 QALYs, at an incremental cost of $962,240.8 per patient. The incremental cost-effectiveness ratio (ICER) is $558,973 per QALY. Subgroup analysis indicated that patients ineligible for cisplatin treatment had a lower ICER compared to those who were eligible for cisplatin.From the perspective of US payers, at a willingness-to-pay threshold of $150,000 per QALY, the combination of EV and pembrolizumab is estimated to not be cost-effective compared to traditional chemotherapy in the first-line treatment of mUC patients. Subgroup analysis indicated that patients ineligible to receive cisplatin had a lower ICER than those who were eligible for cisplatin treatment.